Exposure of wild carnivores to rabies and Mokola viruses in provincial and private game reserves in Mpumalanga province - Sabeta, Claude Taurai (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2014.